DEVELOPMENT OF STANDARD LAYOUT FOR TRADITIONAL BALINESE TEXTILE EXHIBITION TO SUPPORT VISITOR APPRECIATION AND TEXTILE MATERIAL STABILITY - Putu Ari Darmastuti; Yuni Diantari; Kadek Resi Kerdiati (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2026)
Textile preservation presents significant challenges in non-commercial exhibition contexts in Indonesia, particularly in Bali, where many exhibition spaces have yet to implement adequate conservation standards. At the same time, research on exhibition layout design remains fragmented between interior architecture and museum studies, limiting the development of integrated approaches. This gap becomes increasingly important alongside the growing emphasis on sustainability in exhibition practices. This study adopts a qualitative approach through a systematic review of literature published within the last five years. The analysis focuses on the relationship between spatial configuration, environmental control, and textile conservation, aiming to identify design strategies that respond to both material preservation and visitor needs. The findings suggest that textile exhibitions require careful and holistic planning that not only protects fragile materials but also creates a meaningful and comfortable experience for visitors. Key considerations include controlling light exposure, maintaining stable humidity and temperature, and organizing spatial layouts that minimize physical interaction while supporting visual accessibility. Circulation design plays a critical role in achieving this balance. While unstructured layouts encourage exploratory movement, they may lead to overcrowding and uneven distribution. In contrast, directed circulation systems provide better control over visitor flow, viewing duration, and spatial experience, making them more suitable for sensitive textile exhibitions.